Disruption of TFGβ-SMAD3 pathway by the nuclear receptor SHP mediates the antifibrotic activities of BAR704, a novel highly selective FXR ligand. (May 2018) - Carino, Adriana; Biagioli, Michele; Marchianò, Silvia; Scarpelli, Paolo; Zampella, Angela; Limongelli, Vittorio; Fiorucci, Stefano
Graphical abstract: Abstract: Liver fibrosis, a major health concern worldwide, results from abnormal collagen deposition by activated hepatic stellate cells (HSCs) in an injured liver. The farnesoid-x-receptor (FXR) is a bile acid sensor that counteracts HSCs transdifferentiation . While targeting FXR holds promise, 6-ethyl-CDCA known as obeticholic acid, the first in class of FXR ligands, causes side effects, partially because the lack of selectivity toward GPBAR1, a putative itching receptor. Here, we describe the 3-deoxy-6-ethyl derivative of CDCA, BAR704, as a highly selective steroidal FXR agonist. Methods: Liver Fibrosis was induced in mice by carbon tetrachloride (CCl4 ). Main results: In transactivation assay BAR704 activated FXR with and EC50 of 967 nM while exerted no agonistic activity on other receptors including GPBAR1. In naïve mice, BAR704 modulated the expression of FXR target genes in the liver of wild type mice but not in FXR −/− mice. In cirrhotic mice, administration of BAR704, 15 mg/kg for 9 weeks, spared the liver biosynthetic activity (bilirubin and albumin plasma levels), reduced liver fibrosis score (Sirius red staining), expression of pro-fibrogenetic (Colα1α, TGFβ and αSMA) and inflammatory genes (IL-1β, TNFα) and portal pressure. From mechanistic stand point, we have found that exposure of LX2 cells, a human HSCs line, to BAR704 increased the transcription of the short heterodimer partner (SHP) and induced the binding of this nuclear receptor to SMAD3, thus abrogating the binding of phosho-SMAD3 to the TGFβ promoter. Conclusions and applications: BAR704 is a selective FXR agonist that reduces liver fibrosis by interfering with the TGFβ-SMAD3 pathway in HSCs. Selective FXR agonists may represent an attractive strategy for the treatment of liver fibrosis.